A Review of Bundled Payments in Total Joint Replacement. Issue 11 (November 2019) - Manickas-Hill, Olivia; Feeley, Thomas; Bozic, Kevin J.
Abstract : The Bundled Payments for Care Improvement (BPCI) initiative, developed by the U.S. Center for Medicare & Medicaid Innovation, aims to reduce health-care expenditures while maintaining or improving patient outcomes. Several published reports evaluating the impact of the BPCI on payment, utilization, and patient outcomes during the first 3 years of the initiative demonstrated a reduction in Medicare payments for major joint replacement of the lower extremity, driven primarily by a reduction in post-acute care utilization, without a sacrifice in quality of care as measured by no change in unplanned readmission rate, emergency department use, or mortality rate during the 90 days from episode start date. However, this reduction in Medicare payments did not translate into savings to the Medicare program, as the Net Payment Reconciliation Amount (NPRA) to providers was not included in any of the cost analyses. The impact of the BPCI on outcomes important to patients and physicians has not been thoroughly evaluated in the published literature. Important (and standardly trackable) outcome measures that can be considered when assessing the effectiveness of a health-care model for bundled payments for total joint replacement include 30-day postoperative mortality, reoperation, and readmission; hip or knee functional status; hip, knee, or lower back pain; quality of life; work status; and satisfaction with results. Many studies directly evaluated only survival and disutility as manifested by readmission rate and emergency department use. Multiple pilot studies evaluating cost savings and quality measures using a bundled-payment alternative payment model have demonstrated a reduction in Medicare episode payments, primarily related to decreased length of hospital stay and post-acute care utilization. Readmission, certain comorbidities, and low socioeconomic status are associated with higher episode costs. An evaluation of a bundled payment program for orthopaedic procedures in Stockholm, Sweden, revealed a decrease in cost, complication rate, and wait time after the introduction of a bundled payment system. Some of these improvements may be related to an increase in the number of surgical procedures on younger, healthier patients performed at specialized orthopaedic centers, with a concomitant shift of patients with comorbidities to hospitals.